Nutritional Adequacy in Adolescent Towards the Menstrual Cycle - susmini, susmini; Hendian, Feriana Ina; Meliana, Meliana (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Improving the health and well-being of teenagers is essential, especially during puberty. Teenage girls undergo a variety of changes, both physically and mentally. Adequate nutrition is necessary to support the completion of puberty. Menstruation, which involves the shedding of the uterine lining and egg cells is one of primary bodily changes young women experience during puberty. Adolescent girls’ menstrual cycles are influenced by hormonal changes during puberty. Menstrual problems or disorders that need to be known and frequently become complaints include dysmenorrhea (pain during menstruation), menorrhagia (large blood volume during menstruation), amenorrhea (menstruation that abruptly stops for no apparent reason or has not occurred since the age of 16), and oligomenorrhea. This study, conducted at the women's dormitory at Tribhuwana Tunggadewi University in Malang, aimed to assess young women's nutritional adequacy during their menstrual cycle. Utilizing a robust correlational research design, the study was carried out from July to August 2024 to ensure the reliability of the results. A total of 32 respondents participated. Statistical analysis with the Chi-square test yielded significant findings: adolescent girls' BMI had a significantly impacts on nutritional adequacy, with a p-value (2-tailed) of 0.000 (p 0.05). The analysis showed 19 respondents had a normal BMI (59.4%), while 12 (37.5%) were classified as underweight. Additionally, 28 respondents (87.5%) were have adequate nutrition, demonstrating the effectiveness of the study's methodology in assessing nutritional adequacy during the menstrual cycle. It is recommended to increase the number of study sample and examine other factors that may contribute to irregular menstrual cycle.